Animais como cidadãos : a teoria política de direitos animais de Sue Donaldson e Will Kymlicka em Zoopolis - Domingues, Aleska De Vargas (2021)
The aim of this dissertation was to verify if domesticated non-human animals should have their interests considered as citizens. To achieve the general objective, an exploratory bibliographic research was carried out, in which theories on the moral consideration of non-human animals, on the defense of animal rights, and on the defense of an animal policy and the condition of non-human animals domesticated in the human community were analyzed. Citizenship involves the recognition of the individual as a bearer of rights, included and accepted by the legal system, part of the state society. Traditionally, this status is conferred only to humans. The idea of nonhuman citizenship is defended by the philosophers Sue Donaldson and Will Kymlicka and is contained in the work Zoopolis: A Political Theory of Animal Rights (2011) and discussed in later articles and, therefore, the theory was further elaborated in this study. Zoopolis' proposal is part of a recent trend that uses terms from Political Philosophy to seek justice for non-human animals, in a phenomenon that has been called “political turn”. Donaldson and Kymlicka's theory was explored, and their ideas were also opposed to the ethical perspectives of classic and contemporary authors, such as Jeremy Bentham, Peter Singer, Tom Regan, Gary Francione, and to the important criticisms and considerations made by Eva Meijer and Mark Rowlands. Throughout the work, arguments were presented about non-human sentience, about the moral and rights consideration of non-human animals, as well as about the consideration of non-human animals as citizens. Based on such arguments, this study concluded that non-human animals can be thought of as members of society to be protected by rights, regardless of citizen status.